The neoliberal definition of "elite space" in IKEA kitchens. Issue 3 (27th May 2017) - Ledin, Per; Machin, David
ABSTRACT: This paper carries out a social semiotic analysis of an IKEA commercial to show how their contemporary kitchens, despite being market for those on a more modest budget, present an aspirational form of elite space, constructed on the basis of ideas, values and priorities favored by a neoliberal ideology. Using the notions of new writing and technologization, and carrying out an analysis of form, texture and color, we show how the kitchen, its occupants and their actions are designed and represented as a tightly coded and functional whole into which the ideas and values of neoliberalism can be realized. The designs erase personal difference and actual context and in the commercial allow performances which mark aspirational values according to neoliberalism. Here the kitchen space itself, as is usual across IKEA commercials, allows the protagonist to be "creative, " improve his performance, be "dynamic" and "flexible." Yet these, like the objects and textures in the kitchen, are merely symbolic components which appear reasonable in the context of the tightly coded system.